Determination of Thermal Conductivity of Nano-ceramic Thermal Insulation Coating on the Surface of a Heat Pipe - Vafaeva Khristina Maksudovna; Pavlov Mikhail Vasilyevich; Karpov Denis Fedorovich; Mittal Sachin; Kalpana Kilaru; Kataria Ansh; Joshi Ankita; Visweswari Tamminana; Islam Raisul (E3S Web of Conferences)
In the pursuit of conserving non-renewable fuel and energy resources and mitigating harmful emissions into the atmosphere, thermal insulation is commonly employed in practice for heated elements, including but not limited to building exteriors, boilers and furnaces, thermal power equipment, pipelines, and the like. The primary characteristic of any insulation material lies in its thermal conductivity, particularly under operational conditions. The research object is liquid nano-ceramic thermal insulation located on the surface of a round-section pipeline with a circulating heat carrier. The research subject is the thermal conductivity properties of the insulation material under operational conditions. The research aim is to determine the thermal conductivity coefficient of liquid nano-ceramic thermal insulation coating on the surface of the pipeline. The research method involves the laws of steady-state heat conduction and heat transfer for a two-layer cylindrical wall. Research findings indicate that for a steel pipeline measuring 76×3 mm with insulation thickness of 3.5 mm, the thermal conductivity coefficient of the liquid nano-ceramic thermal insulation material amounted to 0.0145 W/(m⋅K). Disregarding the radiative component, the thermal conductivity coefficient equals 0.0135 W/(m⋅K). Conclusions drawn suggest that the obtained value of the operational thermal conductivity coefficient of the liquid nano-ceramic thermal insulation material aligns with the manufacturer's claimed material thermal conductivity of 0.014 W/(m⋅K) and with the findings of other researchers. Minor discrepancies in magnitudes may be attributed to the extended period of insulation usage on the pipeline surface, which at the time of the conducted scientific investigations was approximately 1.5 years.